Fundamentals of the development of Vocational Education and Further Education of VET pedagogues in Sub-Saharan Africa - Eicker, Friedhelm [Verfasser] (My University, 2017)
"For many years, the University of Rostock/Technical Education has supported three universities from Mozambique, Ethiopia and South Africa in their effort to establish a modern educational and further educational programme for VET pedagogues. A Further Education network was established in the first steps. If more German universities support it, this network can expand to various other Sub-Saharan African countries. This still poses the essential question which scientific approach will be the basic position. Furthermore the question is how the Further Education network of universities, vocational schools and other VET institutions should be developed locally in Sub-Saharan Africa. A constructivist approach, which is positioned between academic discipline and vocational science, will be proposed here. In the first place, university lecturers and selected teachers will be able to acquire shaping competence. A "Train the Trainer Further Education System" will be proposed. Fundamentals of the development of Vocational Education and especially of the Further Education of VET teachers in Sub-Saharan Africa will be presented and motivated: the shaping-/competence-based and networked teaching and learning. Expectations on the development of the planned "Train the Trainer Further Education System" will be outlined according to former projects of the University of Rostock/Technical Education. It will be argued for creating and implementing a highly-flexible shaping-/competence-based and networked "Train the Trainer Further Education System"." (author's abstract; BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; P 3.2 Lehrpersonal; I 2.3.1 Afrika; Berufsbildung; Bildungspersonal; Weiterbildungssystem; Subsahara-Afrika; Mosambik; Äthiopien; Südafrika